Building waste caring character: School-based waste management training at SMP Muhammadiyah 10 Yogyakarta - Muhammad Muttaqien; Muhammad Arif Rizqi; Alifya Fathiyyah Nooresa; Dewi Ayu Indahsari; I Wayan Nain Febri (Community Empowerment, 2024)
Since 2010, Muhammadiyah has recognized that waste materials such as plastic, paper, cans, and aluminum still contain energy. One of Muhammadiyah schools that utilizes plastic waste is SMP Muhammadiyah 10 Yogyakarta (Muhdasa) through its "sedekah sampah" (charity waste) task force. However, the task force members are active students who change every year, requiring continuous education. Additionally, there was no centralized collection point for plastic bottles. This community service aimed to enhance students' knowledge about waste types and management, as well as cultivate their environmental consciousness. The method employed involved initial observation followed by socialization in collaboration with the environmental communities Hero Trash Yogyakarta and Akshi UMY. The results show that students gained a better understanding of waste classification and management, as evidenced by their participation in plogging activities (picking up litter while jogging). The activity concluded with the donation of a metal bin for collecting plastic bottles.